Drug Target Exploitable Structural Features of Adenylyl Cyclase Activity in - Andreas N. Mbah; Henri L. Kamga; Omotayo R. Awofolu; Raphael D. Isokpehi (AboutScience Srl, 2012)
The draft genome sequence of the parasitic flatworm Schistosoma mansoni (S. mansoni) , a cause of schistosomiasis, encodes a predicted guanosine triphosphate (GTP) binding protein tagged Smp_059340.1. Smp_059340.1 is predicted to be a member of the G protein alpha-s subunit responsible for regulating adenylyl cyclase activity in S. mansoni and a possible drug target against the parasite. Our structural bioinformatics analyses identified key amino acid residues (Ser53, Thr188, Asp207 and Gly210) in the two molecular switches responsible for cycling the protein between active (GTP bound) and inactive (GDP bound) states. Residue Thr188 is located on Switch I region while Gly210 is located on Switch II region with Switch II longer than Switch I. The Asp207 is located on the G3 box motif and Ser53 is the binding residue for magnesium ion. These findings offer new insights into the dynamic and functional determinants of the Smp_059340.1 protein in regulating the S. mansoni life cycle. The binding interfaces and their residues could be used as starting points for selective modulations of interactions within the pathway using small molecules, peptides or mutagenesis.